Effects of GR 68755 on d-amphetamine-induced changes in mood, cognitive performance, appetite, food preference, and caloric and macronutrient intake in humans. - Johnson, B; Oldman, D; Goodall, E; Chen, Y; Cowen, P (1996)
Pre-clinical studies have suggested that 5-HT(3) antagonists such as GR 68755 oppose mesocorticolimbic dopamine release, which may mediate the important effects of d-amphetamine on positive subjective mood, anorexia, and performance. Twenty-six healthy male volunteers received each of the following treatments in a double-blind, randomized, cross-over design separated by a period of four to seven days: (a) d-amphetamine (20mg orally); (b) placebo; (c) GR 68755 (2mg orally); and (d) GR 68755 plus d-amphetamine. Subjects completed subjective measures of mood, hunger, and satiety. Caloric and macronutrient intake were measured using a test meal. Performance and attention were assessed using standardized computerized tasks. GR 68755 enhanced accuracy on the computerized attention task but failed to reverse significantly any of the effects of d-amphetamine. These results suggest that at these doses GR 68755 pre-treatment does not significantly reduce the effects of d-amphetamine.